(7x X-15):3=2
12x(x+37)=504
88-3(7+x)=64
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)88-3(7+x)=64
=>3(7+x)=88-64
=>3(7+x)=24
=>7+x=24:3
=>7+x=8
=>x=8-7=1
tick nha
1. (7.x-15):3=2 2. 12.(x+37)=504 3. 85-3.(7+x)=64
7.x-15=2.3 x+37=504:12 3.(7+x)=85-64
7.x-15=6 x+37=42 3.(7+x)=21
7.x=6+15 x=42-37 7+x=21:3
7.x=21 x=5 7+x=7
x=21:7 x=7-7
x=3 x=0
1. (7.x-15):3 = 2
(7.x-15)=2.3
(7.x-15)=6
7x=15+6
7x=21
x=21:7
x=3
2.12.(x+37=504
x+37=504:12
x+37=42
x = 42-37
x=5
3. 85-3.(7+x)=64
3.(7+x)=85-64
3.(7+x)=21
7+x=21:3
7+x=7
x=7-7
x=0
a: \(4x^3+12=120\)
=>\(4x^3=108\)
=>\(x^3=27=3^3\)
=>x=3
b: \(\left(x-4\right)^2=64\)
=>\(\left[{}\begin{matrix}x-4=8\\x-4=-8\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=12\\x=-4\end{matrix}\right.\)
c: (x+1)^3-2=5^2
=>\(\left(x+1\right)^3=25+2=27\)
=>x+1=3
=>x=2
d: 136-(x+5)^2=100
=>(x+5)^2=36
=>\(\left[{}\begin{matrix}x+5=6\\x+5=-6\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=1\\x=-11\end{matrix}\right.\)
e: \(4^x=16\)
=>\(4^x=4^2\)
=>x=2
f: \(7^x\cdot3-147=0\)
=>\(3\cdot7^x=147\)
=>\(7^x=49\)
=>x=2
g: \(2^{x+3}-15=17\)
=>\(2^{x+3}=32\)
=>x+3=5
=>x=2
h: \(5^{2x-4}\cdot4=10^2\)
=>\(5^{2x-4}=\dfrac{100}{4}=25\)
=>2x-4=2
=>2x=6
=>x=3
i: (32-4x)(7-x)=0
=>(4x-32)(x-7)=0
=>4(x-8)*(x-7)=0
=>(x-8)(x-7)=0
=>\(\left[{}\begin{matrix}x-8=0\\x-7=0\end{matrix}\right.\)
=>\(\left[{}\begin{matrix}x=8\\x=7\end{matrix}\right.\)
k: (8-x)(10-2x)=0
=>(x-8)(x-5)=0
=>\(\left[{}\begin{matrix}x-8=0\\x-5=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=8\\x=5\end{matrix}\right.\)
m: \(3^x+3^{x+1}=108\)
=>\(3^x+3^x\cdot3=108\)
=>\(4\cdot3^x=108\)
=>\(3^x=27\)
=>x=3
n: \(5^{x+2}+5^{x+1}=750\)
=>\(5^x\cdot25+5^x\cdot5=750\)
=>\(5^x\cdot30=750\)
=>\(5^x=25\)
=>x=2
1) 3x = 45 + 15 = 60
x = 60 : 3 = 20
2) 5x = 50 - 35 = 15
x = 15 : 5 = 3
3) (2x - 5) + 17 = 6
2x - 5 = 6 - 17
2x - 5 = -11
2x = -11 + 5
2x = -6
x = -6 : 2 = -3
4) 10 - 2(4 -3x) = -4
2(4 - 3x) = -4 - 10 = -14
4 - 3x = -14 : 2 = -7
3x = -7 - 4 = -18
x = -18 : 3 = -6
\(\left\{{}\begin{matrix}\left\{{}\begin{matrix}3x-15=45\Leftrightarrow3x=60\Leftrightarrow x=20\\35-5x=50\Leftrightarrow5x=-15\Leftrightarrow x=-3\end{matrix}\right.\\\left\{{}\begin{matrix}\left(2x-5\right)+17=6\Leftrightarrow2x+5=-11\Leftrightarrow2x=-16\Leftrightarrow x=-8\\10-2\left(4-3x\right)=-4\Leftrightarrow8-6x=14\Leftrightarrow6x=-6\Leftrightarrow x=-1\end{matrix}\right.\\\left\{{}\begin{matrix}-12+3\left(-x+7\right)=-18\Leftrightarrow-3x+21=-6\Leftrightarrow-3x=-27\Leftrightarrow x=9\\24:\left(3x-2\right)=-3\Leftrightarrow3x-2=-8\Leftrightarrow3x=-6\Leftrightarrow x=-2\end{matrix}\right.\\-45:5\left(-3-2x\right)=3\Leftrightarrow-15-10x=-15\Leftrightarrow10x=0\Leftrightarrow x=0\end{matrix}\right.\)
a) \(2^x=16\)
\(2^x=2^4\)
\(\Rightarrow x=4\)
vay \(x=4\)
b) \(4^x=64\)
\(4^x=4^3\)
\(\Rightarrow x=3\)
vay \(x=3\)
c) \(15^x=225\)
\(15^x=15^2\)
\(\Rightarrow x=2\)
vay \(x=2\)
d) \(2^x-15=17\)
\(2^x=32\)
\(2^x=2^5\)
\(\Rightarrow x=5\)
vay \(x=5\)
e) \(2^x-64=2^6\)
\(2^x=2^6+64\)
\(2^x=128\)
\(2^x=2^7\)
\(\Rightarrow x=7\)
vay \(x=7\)
f) \(\left(7x-11\right)^3=2^5.5^2+200\)
\(\left(7x-11\right)^3=800+200\)
\(\left(7x-11\right)^3=1000\)
\(\left(7x-11\right)^3=10^3\)
\(\Rightarrow7x-11=10\)
\(\Rightarrow7x=21\)
\(\Rightarrow x=3\)
vay \(x=3\)
a: =428(36+64)=42800
b: =512(47-37)=5120
c: =72x100=7200
( 7.x - 15 ) : 3 = 2
7.x - 15 = 6
7.x = 6 + 15
7.x = 21
x = 3
không biết vì chưa học
88 - 3 ( 7 + x ) = 64
3 ( 7 + x ) = 88 - 64
3 ( 7 + x ) = 24
7 + x = 8
x = 1
(7.x -15):3=2
7.x-15=2.3
7.x-15=6
7.x=6+15
7.x=21
x=21:7
x=3
12.(x+37)=504
x+37=504:12
x+37=42
x=42-37
x=5
88-3(7+x)=64
3(7+x)=88-64
3(7+x)=24
7+x=24:3
7+x=8
x=8-7
x=1
dấu . là nhân nhé